Complications in Maxillofacial Cosmetic Surgery Strategies for Prevention and Management (Springer International Publishing, 2018)
This book is designed to offer practitioners clear, up-to-date guidance on the management of complications associated with maxillofacial cosmetic surgery. The first section provides a detailed overview of general topics relating to cosmetic surgery patients, including assessment, anesthesia and medical complications, wound healing, postoperative infection, pain management, and medicolegal issues. The second section then discusses the nature and management of the complications associated with each maxillofacial cosmetic surgery procedure, from laser treatment and use of neuromodulators and soft tissue fillers to orthognathic surgery, rhinoplasty, neck procedures, rhytidectomy, genioplasty, and facial implants. Complications in Maxillofacial Cosmetic Surgery is multi-authored, multi-institutional, and multi-specialty based. It will be of value for a range of health care providers who practice in the head and neck area, including oral and maxillofacial surgeons, otolaryngologists, plastic and reconstructive surgeons, dermatologists, and cosmetic surgeons.